Efficacy of Second Generation Direct-Acting Antiviral Agents for Treatment Naïve Hepatitis C Genotype 1: A Systematic Review and Network Meta-Analysis. - Thanthima Suwanthawornkul; Thunyarat Anothaisintawee; Abhasnee Sobhonslidsuk; Ammarin Thakkinstian; Yot Teerawattananon (PLoS ONE)
Background The treatment of hepatitis C (HCV) infections has significantly changed in the past few years due to the introduction of direct-acting antiviral agents (DAAs). DAAs could improve the sustained virological response compared to pegylated interferon with ribavirin (PR). However, there has been no evidence from randomized controlled trials (RCTs) that directly compare the efficacy among the different regimens of DAAs. Aim Therefore, we performed a systematic review and network meta-analysis aiming to compare the treatment efficacy between different DAA regimens for treatment naïve HCV genotype 1. Methods Medline and Scopus were searched up to 25th May 2015. RCTs investigating the efficacy of second generation DAA regimens for treatment naïve HCV genotype 1 were eligible for the review. Due to the lower efficacy and more side effects of first generation DAAs, this review included only second generation DAAs approved by the US or EU Food and Drug Administration, that comprised of simeprevir (SMV), sofosbuvir (SOF), daclatasvir (DCV), ledipasvir (LDV), and paritaprevir/ritonavir/ombitasvir plus dasabuvir (PrOD). Primary outcomes were sustained virological response at weeks 12 (SVR12) and 24 (SVR24) after the end of treatment and adverse drug events (i.e. serious adverse events, anemia, and fatigue). Efficacy of all treatment regimens were compared by applying a multivariate random effect meta-analysis. Incidence rates of SVR12 and SVR24, and adverse drug events of each treatment regimen were pooled using 'pmeta' command in STATA program. Results Overall, 869 studies were reviewed and 16 studies were eligible for this study. Compared with the PR regimen, SOF plus PR, SMV plus PR, and DVC plus PR regimens yielded significantly higher probability of having SVR24 with pooled risk ratios (RR) of 1.98 (95% CI 1.24, 3.14), 1.46 (95% CI: 1.22, 1.75), and 1.68 (95% CI: 1.14, 2.46), respectively. Pooled incidence rates of SVR12 and SVR24 in all treatment regimens without PR, i.e. SOF plus LDV with/without ribavirin, SOF plus SMV with/without ribavirin, SOF plus DCV with/without ribavirin, and PrOD with/without ribavirin, (pooled incidence of SVR12 ranging from 93% to 100%, and pooled incidence of SVR24 ranging from 89% to 96%) were much higher than the pooled incidence rates of SVR12 (51%) and SVR24 (48%) in PR alone. In comparing SOF plus LDV with ribavirin and SOF plus LDV without ribavirin, the chance of having SVR12 was not significantly different between these two regimens, with the pooled RR of 0.99 (95% CI: 0.97, 1.01). Regarding adverse drug events, risk of serious adverse drug events, anemia and fatigue were relatively higher in treatment regimens with PR than the treatment regimens without PR. The main limitation of our study is that a subgroup analysis according to dosages and duration of treatment could not be performed. Therefore, the dose and duration of recommended treatment have been suggested in range and not in definite value. Conclusions Both DAA plus PR and dual DAA regimens should be included in the first line drug for treatment naïve HCV genotype 1 because of the significant clinical benefits over PR alone. However, due to high drug costs, an economic evaluation should be conducted in order to assess the value of the investment when making coverage decisions.